SIMULASI PENGARUH JUMLAH DAN PANJANG SUDU TERHADAP DAYA TURBIN ANGIN TIPE POROS HORISONTAL - Josua Simanjuntak; Stenly Tangkuman; Irvan Rondonuwu (JURNAL POROS TEKNIK MESIN UNSRAT, 2021)
Wind power is a power plant that uses wind as an energy source to produce electrical energy. This plant converts wind energy into electrical energy using wind turbines or windmills. The purpose of this study was to obtain the simulation result of comparison wind turbine power on variations number and length. The conclusion of this study is increasing number and length of sudus in the Ansys 2020 R1 simulation, the greater power produced. The greatest power was obtain in the variation of the turbine with a number of sudus 6 and 2 meter of length is 1290 Watt.Keywords: Horizontal axis wind turbine, Simulation, Power, Torque